Spectrophotometric Estimation of Sulfadoxine in Pharmaceutical Preparations - Sangita Sharma; Madhurjya Neog; Vipul Prajapati; Hiren Patel; Dipti Dabhi (E-Journal of Chemistry)
Four simple, sensitive, accurate and rapid visible spectrophotometric methods (A, B, C and D) have been developed for the estimation of sulfadoxine in pharmaceutical preparations. They are based on the diazotization of sulfadoxine with sodium nitrite and hydrochloric acid followed by coupling with N-(1-naphthyl) ethylenediamine dihydrochloride (Method A) to form pink coloured chromogen, diphenylamine (Method B) to form light pink coloured chromogen, chromotropic acid (in alkaline medium) (Method C) to form orange coloured chromogen, Resorcinol (in alkaline medium) (Method D) to form light orange coloured chromogen and exhibiting absorption maxima (λmax) at 536 nm, 524 nm, 520 nm and 496 nm respectively. The coloured chromogens formed are stable for more than 2 h. Beer’s law was obeyed in the concentration range of 1.0 - 5.0 μg/mL in Method A , 5.0 - 25.0 μg/mL in Method B, 5.0 - 25.0 μg/mL in Method C and 4.0 - 8.0 μg/mL in Method D respectively. The results of the three analysis have been validated statistically and by recovery studies. The results obtained in the proposed methods are in good agreements with labeled amounts, when marketed pharmaceutical preparations are analyzed.